2022
DOI: 10.1109/access.2022.3165199
|View full text |Cite
|
Sign up to set email alerts
|

Complexity Analysis of EEG in Patients With Social Anxiety Disorder Using Fuzzy Entropy and Machine Learning Techniques

Abstract: The diagnosis of social anxiety disorder (SAD) is of great consequence not only due to its impacts on the individual and society but also the expenditures to the national health systems. There is yet a deficiency of objective neurophysiological information to assist the present clinical SAD diagnosis. The main objective of this study is to analyze the electroencephalogram (EEG) complexity of 88 SAD subjects, subdivided into 4 balanced groups (22 severe, 22 moderate, 22 mild, and 22 healthy controls (HCs) using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 71 publications
(57 reference statements)
0
9
0
Order By: Relevance
“…Features from these frequency bands were chosen to provide optimum accuracy with optimal order. The appropriate order (p) of the model was calculated by the Akaike Information Criterion (AIC) as described in our previous studies ( 20 , 26 , 45 ). In this study, the optimum order is 5.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Features from these frequency bands were chosen to provide optimum accuracy with optimal order. The appropriate order (p) of the model was calculated by the Akaike Information Criterion (AIC) as described in our previous studies ( 20 , 26 , 45 ). In this study, the optimum order is 5.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, we applied machine learning techniques to study the EEG complexity ( 26 ) and deep learning models with PDC features ( 27 ) to classify four different subtypes of SAD. Our study found that the deep learning model outperformed the machine learning models, achieving a classification accuracy of 92.86% using a combination of CNN and LSTM, and the most important features for classification were located in the default mode network (DMN) of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…(1) Compared with the Young_GAD patients, the Old_GAD patients had higher AP and FE values in beta rhythm in most brain regions, and there were significant statistical differences in the forehead, central, and parietal regions. The increased AP value of beta indicated that the brain activity is in a state of tension and neural nervousness, and the increased FE value indicated increased complexity ( Al-Ezzi et al, 2022 ). Shen et al (2022) has revealed that GAD patients have higher PSD and FE than healthy adults in beta rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…The Food and Drug Administration 4 (FDA4) approved the value of theta/beta as a biomarker for attention deficit and hyperactivity disorder (ADHD) ( Newson and Thiagarajan, 2019 ). Al-Ezzi et al (2022) showed that the FE value of social anxiety disorder (SAD) in beta rhythm was positively correlated with the Social Interaction Anxiety Scale (SIAS). On the other hand, more evidence also points to a high correlation between EEG characteristics of beta rhythm and age change.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, functional solutions have been proposed, including the definition of biomarkers that can distinguish between these diseases, which may contribute to both correct diagnosis and selection of appropriate therapy, and also it could play a role in tracking patient status [12,13]. The promising biomarkers are described in different psychiatric disorders and include alterations in the genetic, epigenetic, structure, function of the brain, endocrine system, immune system, and neuropsychological aspects [13,14,15,16].It is widely accepted that social phobia is a polygenic and complex condition, however, few altered genetic and epigenetic factors are identified as causative agents.…”
Section: Introductionmentioning
confidence: 99%